(untitled) (Research, Society and Development, 2022)
The elderly, because they undergo changes with advancing age, end up suffering compromises that affect their health, causing diseases. The group of diseases that most affect this population are the group of chronic diseases. The objective of this study is to identify the main barriers encountered by elderly people living with chronic diseases. This is a literature review carried out from December 2021 to February 2022. Conducted through a search in the SCIELO and LILACS databases using the health descriptors Difficulties AND Elderly AND Chronic Diseases. For better results, inclusion and exclusion criteria were defined. After the eligibility criteria, the findings were read, totaling 12 studies used. It was possible to observe that there are several barriers encountered by the elderly with some diagnosis of this group of diseases. The level of education, inadequate diet, lack of physical activity and correct adherence to medications contribute to the control of these pathologies and most elderly people end up having difficulty in adhering to these methods, as they often find their functionality compromised.